Pengaruh Metode Make A Match Terhadap Aktivitas, Minat dan Hasil Belajar Siswa pada Pembelajaran IPA - Herisnawati Herisnawati; Siti Nurhidayati; Tri Sari Wijayanti (IKIP Mataram, 2015)
The study aims to determine the effect of the Make A Match method on the activities, interests, and learning outcomes of class VIII students of MTs Darussalam Bermi West Lombok. The population in this study were all eighth-grade students of MTs Darussalam Bermi, while the study sample was 58 students. Class VIII C as the experimental class and class VIII D as the control class. The sampling technique uses purposive sampling. The research instrument used was an observation sheet to obtain data on learning activities, questionnaires for learning interest data, and tests for student learning outcomes. Based on the results of the analysis of student activity data in the control class, an average value of 71 was obtained with the active category, while the experimental class obtained an average value of 78 with a very active category. The average learning interest of students in the control class is 36.39 with a less high category, then in the experimental class, the average student interest is 45.73 with a fairly high category using the Make A Match method. Analysis of student learning outcomes data obtained an average value in the experimental class of 82.4 with the highest value of 100 and the lowest 72, while the average value of the control class was 76.1 with the highest value 88 and the lowest value 64. Based on the results of the t-test obtained t count is 17.43 and t table is 1.67, because tcount ≥ ttable, then there are differences in activities, interests, and learning outcomes using the Make A Match method in class VIII students of MTs Darussalam Bermi. Based on these results it can be concluded that there is an effect of the Make A Match method on science learning outcomes of class VIII students of MTs Darussalam Bermi.